2005
DOI: 10.2174/1573406054368710
|View full text |Cite
|
Sign up to set email alerts
|

QSAR of the Anticonvulsant Enaminones; Molecular Modeling Aspects and other Assessments

Abstract: The enaminones represent potentially useful agents for the clinical treatment in generalized tonic-clonic seizures (Epilepsia, 1993, 34(6), 1141-1145, Biopharm. Drug Disp. 2003, 397-407). A regression analysis was performed to provide a quantitative structure-activity relationship (QSAR) correlation model for prediction of activity for the anticonvulsant enaminones. Molecular modeling was performed to determine the molecular confluence of the Unverferth model (J. Med. Chem. 1998, 41, 63-73) to the enaminones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Previously, we reported on the correlation between CLog P and the anticonvulsant activity of our enaminone derivatives. It is known that the lipophilicity of various compounds is associated with the biological activity 18. Thus, the numerical data used in this study to develop the CoMFA and CoMSIA models were the CLog P values for each molecule 8,21.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported on the correlation between CLog P and the anticonvulsant activity of our enaminone derivatives. It is known that the lipophilicity of various compounds is associated with the biological activity 18. Thus, the numerical data used in this study to develop the CoMFA and CoMSIA models were the CLog P values for each molecule 8,21.…”
Section: Resultsmentioning
confidence: 99%
“…The anticonvulsants phenytoin and carbamazepine prolong the inactive state of the VGSCs, and more recently, lamotrigine, zonisamide, and rufinamide have appeared and their modes of action suggest an involvement of sodium channel blockade 33. In our studies on the anticonvulsant activity of the enaminones6, 7, 14, 34–44 we found that they act as inhibitors of the VGSCs 31, 38. In our work on analogues of the classic pharmacophore, 35 , it was noted that anticonvulsant activity was maintained when R = H, CH 3 , C 2 H 5 , or C(CH 3 ) 3 and when X = + σ 35.…”
Section: Synthetic Studies and Qsar Analysis Of The Enaminonesmentioning
confidence: 61%
“…1 H NMR (CDCl 3 ) δ 5.26 (d broad, J ≈ 7.0 Hz, 2H, NH), 4.10 (m, 2H, CH), 3.77 (s, 6H, O-CH 3 ), 1.45 (d, J ) 7.1 Hz, 6H, CH 3 ). 13…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of rational methodologies of design that need the knowledge of the mechanism of action of the active compounds is limited because most of the AEDs interact with more than one receptor. The alternative rational design of new AEDs based on pharmacophoric patterns overcome this difficulty as it works on the optimization of the potency of a particular mode of action and is therefore broadly used in the discovery of new chemical entities. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation